Inducing and Administering Tregs to Treat Human Disease - Perdigoto, Ana Luisa; Chatenoud, Lucienne; Bluestone, Jeffrey A.; Herold, Kevan C. (Frontiers in Immunology, 2016)
Regulatory T cells control unwanted immune responses including those that mediate tolerance to self as well as to foreign antigens. Their mechanisms of action include direct and indirect effects on effector T cells and important functions in tissue repair and homeostasis. Regulatory T cells express a number of cell surface markers and transcriptional factors that have been instrumental in defining their origins and potentially their function. A number of immune therapies such as rapamycin, IL-2, as well as anti-T cell antibodies are able to induce regulatory T cells and are being tested for their efficacy in diverse clinical settings with exciting preliminary results. However, a balance exists with the use of some, such as IL-2 that may have effects on unwanted populations as well as promoting expansion and survival of regulatory T cells requiring careful selection of dose for clinical use. The use of cell surface markers has enabled investigators to isolate and expand ex vivo regulatory T cells more than 500-fold routinely. Clinical trials have begun, administering these expanded regulatory T cells to patients as a means of suppressing autoimmune and alloimmune response and potentially inducing immune tolerance. Studies in the future are likely to build on these initial technical achievements and use combinations of agents to improve the survival and functional capacity of regulatory T cells.